Granma adolescents´ fertility in the 2015-2020 period - Arelis Rosalen Mora Pérez (Medisur)
Background: Cuban fertility is below replacement, a condition that has been maintained for more than four decades. The values of the adolescent fertility rates do not correspond to the fertility level of the country. Granma province in 2020 had the highest adolescent fertility rate in the country, a behavior that persists for several years. Objective: to describe the behavior of adolescent fertility in Granma and its territories during 2015-2020. Methods: a descriptive cross-sectional study on mothers under 20 years of age in Granma province during 2015-2020. The specific rates for this age group, relative weight of adolescent fertility, according to the area of residence, were taken into account, and those born with low weight from adolescent mothers were analyzed. Results: Granma province and its municipalities show high adolescent fertility values, above the national average. There was an increase in the values of the relative rates and weights in the period of analysis, as well as in the percentages of low birth weight children of adolescent mothers. In rural areas, the values of the selected indicators were higher. Conclusions: actions should be integrated to reduce fertility and adolescent pregnancy in the province. Although there are sexual and reproductive health education programs, the work of the institutions must be integrated to reduce this behavior in adolescent girls.